Pendampingan Pengembangan Modul Kontekstual Berbasis Kearifan Lokal Untuk Guru Madrasah Ibtidaiyah - Nurul Agustin; Ria Resti Fauziah; Rahmat Rudianto; Ainul Fithriyah; Muhammad Luthfi Efendi (LP3M IAIFA Kediri, 2025)
This Community Service Program (PKM) aims to enhance the professional competence of Madrasah Ibtidaiyah (MI) teachers in Menganti District through the development of contextual thematic modules based on local wisdom. The activity was initiated from a needs assessment indicating that most teachers still relied on nationally published modules without adapting them to the social and cultural context of their students. The implementation adopted a Participatory Action Research (PAR) approach consisting of four stages: planning, action, observation, and reflection. Data were collected through semi-structured interviews, Focus Group Discussions (FGD), participatory observations, and document analysis of the developed modules, then analyzed using qualitative and descriptive quantitative methods.The results revealed a significant improvement in teachers’ pedagogical competence and creativity, with 90% of participants actively engaging in discussions, contributing local ideas, and demonstrating a better understanding of contextual module structures. The quality of the developed modules achieved an average score of 85.6% (categorized as very good), compared to only 68.3% (fair) for the publisher’s modules. Furthermore, the activity led to the establishment of the MI Menganti Module Developer Community (KPM-MI) as a collaborative platform for continuous development. This PKM program contributes to transforming learning practices into more contextual, reflective, and teacher-empowering approaches. Collaboration among lecturers, madrasahs, and educational communities emerged as a key factor in fostering innovative learning aligned with the Merdeka Curriculum.